Management of postburn flexion contracture of the proximal interphalangeal joint of the finger by distraction histiogenesis and release and skin grafting: A comparative study - Sanjay Kumar; Sharadendu Sharma; Harish Sharma (Wolters Kluwer Medknow Publications, 2019)
Introduction: Flexion contractures of the fingers cause functional and esthetic problems to a burn patient. Various methods of reconstruction have been described, but the usual treatment for these contractures is release and split-skin graft. In this study, technique of distraction histiogenesis was used for the treatment of finger contracture. Methods: In this study, sixty patients of postburn contracture of proximal interphalangeal (PIP) joint of the hand due to volar skin burns were taken. Thirty patients were treated with distraction technique and thirty patients with release and split-skin grafting. The average age of patient is 20 years. Results: Both techniques showed improvement in range of motion at PIP joint. Esthetic result was also assessed using score on the Visual Analog Scale, with better score in distraction histiogenesis. There was no recurrence of contracture at 6 months follows-up. Conclusion: Technique of gradual distraction histiogenesis is safe for treating long-standing flexion contracture of the finger without risk of neurovascular compromise to finger.